Application of phase changing materials in a CSP plant for thermal energy storage: A review on recent developments. (2022) - Banerjee, Bikash; Chatterjee, Sushovan; Datta, Jinia; Saha, Sabarni Dutta
Abstract: Solar thermal energy storage (TES) is a potent field of research in recent time and it has been attracting researchers all over the world. A lot of work has been done in this field. The main method of storing solar energy is to accumulate solar thermal energy using phase change materials (PCMs) in the latent heat thermal energy storage (LHTES) system. In this paper investigation of recent technologies used in storing solar thermal energy, particularly in concentrated solar power (CSP) plants by using PCMs has been discussed. Thermal properties, that is, latent heat, specific heat, melting point are the main parameters of different PCMs for the TES system. Three issues have been discussed depending on various research papers published on this topic taken into account state-of-the-art understanding and developments. The first part is different PCMs used for thermal energy storage. In the second part, the latest evolution of encapsulation technologies of PCMs has been discussed. The rest of the part is about cost issues and the contrast between latent and sensible TES systems. The present article will be very thoughtful as a good reference to the engineers and researchers for utilization and selection of various PCMs in the heat storage industry, especially the solar thermal power industry.